Analisis Keberhasilan Implementasi Program Pertanian Perkotaan di Kelurahan Lakarsantri Kota Surabaya - Ardyan Rakhmad Pradana; Wahyu Nurharjadmo (Program Studi Ilmu Administrasi Negara Fakultas Ilmu Sosial dan Politik Universitas Sebela, 2021)
The city of Surabaya has a complex problem, namely the poverty rate and the narrowing of productive land, so to deal with it, the City of Surabaya implements an Urban Farming policy program. This research aims to analyze the factors that influence the successful implementation of the urban farming program in Lakarsantri Village by using theory from George C. Edward III. Some of the factors examined were factors of communication, resources, disposition, and bureaucratic structure. This study used a descriptive qualitative research method. Data collection was carried out by interviewing, documenting, and observing. The data analysis process used interactive analysis, namely data reduction, data presentation, and drawing conclusions. The results showed that the success of the urban farming program in Lakarsantri was due to communication factors that went well, clearly, and consistently; qualified resources such as farmer groups, land procurement, seedlings, training budgets and agricultural equipment, open disposition of executor and successful build trust among all parties, as well as directed bureaucratic structures.In general, turban farming programs apart from expanding productive land in the Surabaya area also help the economy of some communities and increase beneficial productive activities. good for the community, government, and also the environment. This condition is expected to serve as an example for other areas that have similar obstacles in running an agricultural sector in urban areas.